Determination of Design Solutions to Overcome the Daylighting Design Failure Observed in Existing Educational Building - Asniza Hamimi Abdul Tharim,; Wan Abdullah, Wan Nur Hanani; Asmat Ismail,; Asmalia Che Ahmad, (International Journal of Sustainable Construction Engineering and Technology, 2022)
Malaysia is blessed with abundant natural light throughout the year. However, as buildings absorb heat from it, the amount of energy required for cooling purposes increases, which is one of the causes of electricity consumption. This research focused on investigating daylight level with a variety of case study classroom characteristics that contribute to daylighting design failure factors. Hence, indoor and outdoor daylight levels were measured for five (5) days in each of the classrooms through field measurement method. The observation was conducted simultaneously with the field measurement to assess the obstacles to implementing efficient daylighting strategies in the classrooms. The results show that the daylight performance for all of the case study classrooms was not within the prescribed suitable range as specified in MS1525 (2019). The classroom design is insufficient to manage daylight in classrooms, which is the most likely reason for the poor illuminance level results. Furthermore, the amount and performance of daylight in the classroom are influenced by the classroom's specific design. The main factors leading to design failures, according to the observation analysis are poor classrooms orientation, double-loaded buildings with single-loaded windows, small glazing areas, low window placement, inappropriate glazing properties, and low light reflectance value. Based on the failure criteria stated, the best practices of classroom daylighting design were found. Furthermore, this study makes a few recommendations to increase the daylight value in all classrooms. This research identified problems that impact low daylight performance in educational buildings and should be used to raise awareness of the benefits of daylight for occupants.